Innovation in Swedish hotels. Issue 6 (13th June 2018) - Wikhamn, Wajda; Armbrecht, John; Remneland Wikhamn, Björn
Abstract : Purpose: The purpose of this paper is to assess innovation in the hotel sector in Sweden and to investigate how structural and organizational factors influence hotel's likelihood of producing service/product, process, organizational and marketing innovations. Design/methodology/approach: This paper is based on responses from 174 hotels with membership in the Swedish hotel association. Responses were collected via a web-based survey. Findings: This paper provides insights about the nature and extent of innovations in the hotel sector. Although traditionally considered rigid and non-innovative, around half of the responding hotels produced at least one type of innovation. Most common are service/product and marketing innovations. A hotel's likelihood of innovating depends largely on structural independence (non-chain), having an explicit innovation strategy and investing in non-traditional R&D. Research limitations/implications: Because of the chosen design (convenience sampling), the results of this paper may lack generalizability. Therefore, future research is encouraged to test the hypotheses further. Practical implications: Managers in the hospitality industry can influence the production of innovations in the hotel sector. By promoting flexibility, defining and communicating an innovation strategy, and engaging in non-traditional R&D activities, practitioners can better respond to the changing business environment. Originality/value: This paper presents a systematic, and internationally recognized, method for assessing four types of innovation in the hotel sector. Its originality stems also from its approach to investigating how key structural and organizational factors, when considered in the same analysis, predict service/product, process, organizational and marketing innovations.